Effective geophysical methodology for investigation of a complex landslide system in Valjevo, Serbia - Petrovic, S.; Markovic, M.; Komatina, S.; Suto, K.; Burazer, M.; Urosevic, Milovan (2017)
Torrential rainfall occurred at the end of May 2014 across Serbia, and Bosnia and Herzegovina (BiH) triggered thousands of new landslides. Shortly after a diverse group of geoscientists united to investigate this phenomenon. The methodology used to study and characterize landslides consisted of a combination of highresolution seismic profiling, resistivity measurements, refraction tomography and MASW, all conducted along the same track. All body wave related investigations were extracted from a high-resolution, high-density seismic reflection survey. This approach enabled us to study many different landslides in a short period of time. Joint analysis of seismic and electric measurements allowed us to characterize important structures, local discontinuities, geometry of the near surface layers and architecture of a landslide. Reactivation potential was studies through time lapse geophysical measurements that proved to be difficult to accomplish with satisfactory repeatability in populated areas.